(untitled) (EU and comparative law issues and challenges series (ECLIC), 2023)
Digitalization is the future and the future is now. New commercial possibilities in the digital market are constantly being explored and exploited. Phenomena such as ecommerce automation and the impact of big data use on transformation of retailer-consumer relationship are increasingly present and more familiar by the day. With them, new perspectives to render consumers vulnerable arise. The digital vulnerability, unlike other types of consumer vulnerability is a state typical of every consumer in the digital market. This notion challenges the existing consumer law and policy’s ability to address the issues that arise in relation to such vulnerability with the traditional perspective. It also questions whether the redesign in the architecture of digital marketplaces is making the traditional architecture of dispute resolution obsolete. With these issues as a starting point, the paper assesses the current trend of streamlining consumer dispute resolution to AI tools and touch screen justice. We argue that under the current set up, instead of providing access to justice that is more available to consumers, this trend has a potential to generate a systemic vulnerability in itself.